Terms in Popular Science Communication: The Case of TV Documentaries - Jaki, Sylvia (HERMES - Journal of Language and Communication in Business, 2018)
Science documentaries on television aim to provide easy and entertaining access to research findings. To do so, producers need to know how to explain complex content for non-expert audiences in a comprehensible way. At the same time, they have to decide what aspects of a subject might be relevant for viewers, or how the subject matter could be rendered more interesting by employing strategies such as personalisation or emotionalisation. One specific decision concerns the use of terms. Both existing research and journalistic handbooks suggest that terms should be or are, in fact, avoided in popular science contexts. However, there is only little empirical research on the topic. This contribution seeks to test several pre-existing hypotheses on terms in documentaries for adults and show how often terms are used and whether/how they are explained when they appear. Examining terms in four English and four German science documentaries, the analysis points out which communicative resources are used to facilitate the comprehension of terms, and where an explanation seems to focus primarily on entertainment rather than ease of comprehension. The results challenge some of the previous views on terms in popular science communication and reveal that documentaries display highly idiosyncratic strategies when it comes to the use of terms.